Analysis of a PV Window for Building Integrated Photovoltaic (BIPV) Applications - Serrano-Casares, Francisco Víctor; Navas Frías, Verónica (My University, 2019)
An amorphous silicon photovoltaic module encapsulated between two transparent glass sheets, an air chamber and a second double glass sheet with an air chamber forms the photovoltaic window. Everything is framed in a PVC structure. The effective dimensions of the a-Si photovoltaic module are 0,57 m x 1,17 m, equivalent to a standard measurement of 0,60 m x 1,20 m. To know the electrical characteristics of PV window in standard test conditions, a test in accordance with IEC standard 61646 and 61215 was carried out. A peak power of 50,74 Wp was obtained and a power uncertainty of ± 6,78% was found. The PV window was placed in a test bench installed on the rooftop of the building of the Andalusian Institute of Renewable Energies, at Málaga (36,73 N; 4,55 W). The test bench allows an adjustment of both azimuth and inclination. A pyranometer was used to measure the global irradiance on the window plane, and a temperature sensor measures its temperature. The photovoltaic window was placed in vertical position facing South. A protocol for data collection that allows knowing the instantaneous power generated by the photovoltaic window has been developed. The irradiance received in a sunny day on the plane of the photovoltaic window was 4114 Wh/m2 and the energy produced was 71,2 Wh. These values are consistent with radiation data obtained from databases and the power value obtained from PV window under standard test conditions. The production of electricity, the economic savings, and CO2 emissions avoided will be analyzed if PV semi-transparent windows were used to replace the glazing skylight of the Industrial Engineering School of Malaga. It will result a BIPV system of 122,73 kWp that could produce 198 MWh per year, save € 27738 and avoid the emission into the atmosphere of 76 tons of CO2.
Keywords: Photovoltaic window; Energy saving; Self consumption